Equivalent circuit model for the strain sensing characteristics of multi-walled carbon nanotube/polyvinylidene fluoride films in alternating current circuit. (April 2018) - Zhao, Chaoyang; Yuan, Weifeng; Liu, Haidong; Gu, Bin; Hu, Ning; Alamusi,; Ning, Youjun; Jia, Fei
Abstract: In this study, multi-walled carbon nanotube/polyvinylidene fluoride (MWCNT/PVDF) composite films fabricated by solution casting method were used to make composite sensors for large strain measurement. The strain sensing characteristics of the sensors in direct current (DC) and alternating current (AC) circuits were both investigated through experiment. It is observed that the piezoresistivity of the MWCNT/PVDF composite films in DC circuits can be used for strain sensing, but this type of application may be limited since the strain-resistance relationship of the films is highly nonlinear. On the other hand, in AC circuits, the change rate of the dielectric loss tangent (DLT) of the composite is also sensitive to the strain. Besides, the experimental results show that the dependence between the strain and the DLT change rate becomes linear if the MWCNT content and the AC frequency are chosen properly. In this work, an equivalent RLC circuit model of the MWCNT/PVDF composite was proposed to interpret the findings obtained from the experiment. The good agreement between the analytical results and the measurements indicates that the current research reveals a new mechanism for the design of high-performance strain sensors. Graphical abstract: Image